Clinical Profile of Acute Coronary Syndrome Patients in Kupang: a Result from 1-Year iSTEMI Registry - Adam, Aditya Angela; Tiluata, Leonora Johana; Yunita, Lowry; Putra, Magma Purnawan; Wilujeng, Niva; Homalessy, Leonita Vivian; Hutabarat, Daniel Christian Fernandez (The Indonesian Heart Association, 2021)
Background: Cardiovascular diseases (CVDs) have been the leading cause of global deaths over the years. In Indonesia, coronary heart disease (CHD) is the most common CVDs, responsible for 29% of all deaths in 2017. East Nusa Tenggara is one of the provinces in Indonesia with the highest prevalence of CHD, which corresponded with growing cases of acute coronary syndromes (ACS). Therefore, we develop a registry to obtain patients' profiles as a basis for strategy development in ACS management. Methods: A retrospectively observational study was conducted on all patients who presented with ACS between January 2019 and September 2020 at a general hospital in Kupang, East Nusa Tenggara. Data collected include demography, patient awareness and transfer history, risk factors, physical findings, diagnosis, workup, treatment, and mortality. Results: A total of 282 patients with ACS (STEMI, 41,2%; NSTEACS, 58,8%) were included in this study. Most patients were male with a mean age of 58,2 ± 12,2 years and normal BMI (32.6%). Nearly 50% of all ACS patients have one or more comorbidities, followed by relatively low adherence to therapy. Half of the patients were referred, but only 16,9% of patients arrived at the first medical facility less than 1 hour after onset. Patients with NTSEACS had more risk factors than patients with STEMI. The median LOS was five days (range, 1-17 days) with 2,8% in-hospital death. The presence of patient and system delay might contribute to the low number of STEMI patients who received reperfusion therapy. Conclusions: This research serves as the primary data for the improvement of acute coronary syndrome management in Kupang and East Nusa Tenggara.